SPE Asia Pacific Oil and Gas Conference and Exhibition 2008
DOI: 10.2118/116915-ms
|View full text |Cite
|
Sign up to set email alerts
|

Early Reservoir Management Insights from the Enfield Oil Development, Offshore Western Australia

Abstract: Integration of key information in the early life of the Enfield water-flood development project led to improved understanding of the reservoir's architecture and dynamic behavior. This paper provides an overview of the field and a review of the first two years of production from the Enfield reservoir including start up of the field, water injection optimisation, acquisition and interpretation of Australia's first time lapse '4D' seismic survey, key well and reservoir performance learnings, use of chemical trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Hurren et al (2012) described how inter-well tracers were used in the Stybarrow Field to characterise producer-injector pair connectivity and transit times. A similar application is described by Hamp et al (2008) in Enfield. Napalowski et al (2012) demonstrated the use of inflow tracers in several key wells in Pyrenees for surety in wellbore cleanup completion (oil soluble tracer) and timing and location of water breakthrough (water soluble tracer) in horizontal production wells.…”
Section: Tracersmentioning
confidence: 92%
“…Hurren et al (2012) described how inter-well tracers were used in the Stybarrow Field to characterise producer-injector pair connectivity and transit times. A similar application is described by Hamp et al (2008) in Enfield. Napalowski et al (2012) demonstrated the use of inflow tracers in several key wells in Pyrenees for surety in wellbore cleanup completion (oil soluble tracer) and timing and location of water breakthrough (water soluble tracer) in horizontal production wells.…”
Section: Tracersmentioning
confidence: 92%
“…Produced gas is compressed and injected into the gas cap, excluding fuel gas for power generation. (Ali et al 2008, Hamp et al 2008 …”
Section: Spe 127394mentioning
confidence: 99%